Informe Argentina - Barzola, Erika Judith; Ejarque, Mercedes; Gonzalez, Leticia; Wahren, Juan; Petz, María Inés; Calvo, Claudia (CLACSO, 2026)
Boletín del Grupo de Trabajo Estudios críticos del desarrollo rural